1987
DOI: 10.1139/v87-311
|View full text |Cite
|
Sign up to set email alerts
|

Studies in iridoid chemistry and spruce budworm (Choristoneurafumiferana) antifeedants

Abstract: Several compounds derived from aucubin and catalposide were prepared and tested for spruce budworm antifeeding activities. Definite biological activity was observed for compound 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…No significant difference was found between the compounds in the second set of biological assays ( reared from second instar on test diets was significantly retarded by compounds 14, 21, 28, and 13, but not by the other compounds. The levels of activity of these compounds are comparable to that of compound 8 reported previously (1).…”
supporting
confidence: 85%
See 3 more Smart Citations
“…No significant difference was found between the compounds in the second set of biological assays ( reared from second instar on test diets was significantly retarded by compounds 14, 21, 28, and 13, but not by the other compounds. The levels of activity of these compounds are comparable to that of compound 8 reported previously (1).…”
supporting
confidence: 85%
“…In the case of the spruce budworm, we previously found that the iridoid derivative 8 has moderate but definite antifeeding activity (1). In this paper, we report on the synthesis of a number of oxygenated decalins and examine them as potential antifeedants against spruce budworm.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The spruce budworm, Choristoneura fumiferana, inflicts severe damage to the forest resource in Canada (1). A strategy that has been considered for the control of spruce budworm is to employ antifeedants to interfere with larval feeding behaviour (2)(3)(4). The approach offers the potential advantage that antifeedants could protect current year foliage while leading indirectly to budworm mortality without being generally toxic (5).…”
Section: Chemical Synthesismentioning
confidence: 99%